Immunopathological Features of Canine Myocarditis Associated with Leishmania infantum Infection. (19th June 2016) - Costagliola, Alessandro; Piegari, Giuseppe; Otrocka-Domagala, Iwona; Ciccarelli, Davide; Iovane, Valentina; Oliva, Gaetano; Russo, Valeria; Rinaldi, Laura; Papparella, Serenella; Paciello, Orlando
Abstract : Myocarditis associated with infectious diseases may occur in dogs, including those caused by the protozoa Neospora caninum, Trypanosoma cruzi, Babesia canis, and Hepatozoon canis . However, although cardiac disease due to Leishmania infection has also been documented, the immunopathological features of myocarditis have not been reported so far. The aim of this study was to examine the types of cellular infiltrates and expression of MHC classes I and II in myocardial samples obtained at necropsy from 15 dogs with an established intravitam diagnosis of visceral leishmaniasis. Pathological features of myocardium were characterized by hyaline degeneration of cardiomyocytes, necrosis, and infiltration of mononuclear inflammatory cells consisting of lymphocytes and macrophages, sometimes with perivascular pattern; fibrosis was also present in various degrees. Immunophenotyping of inflammatory cells was performed by immunohistochemistry on cryostat sections obtained from the heart of the infected dogs. The predominant leukocyte population was CD8+ with a fewer number of CD4+ cells. Many cardiomyocytes expressed MHC classes I and II on the sarcolemma. Leishmania amastigote forms were not detected within macrophages or any other cell of the examined samples. Our study provided evidence that myocarditis in canine visceral leishmaniasis might be related to immunological alterations associated with Leishmania infection.